“Victorian Times Reimagined: The case of 80 Days” - Cátia Ferreira (VIA PANORAMICA: Revista de Estudos Anglo-Americanos / A Journal of Anglo-American Studies, 2025)
Digital games have emerged as a viable medium for reimagining historical myths and narratives through interactive storytelling. As Heilmann and Llewellyn (2010) argue, neo-Victorian media often engage critically with the past, blending historical memory with postcolonial and gendered critique. This article explores how the critically acclaimed digital game 80 Days (2014) reimagines Victorian tales through its branching narrative and distinctive steampunk aesthetics, promoting a critical reinterpretation of Victorian values. Departing from a traditional retelling of Jules Verne’s Around the World in Eighty Days (1873), the game presents an alternate history shaped by speculative technology and global perspectives. Drawing on Fraser’s (1998) analysis of the Victorian quest romance and Campbell's (1949) concept of the monomyth, the study examines how 80 Days both adopts and subverts classical narrative structures. The game’s thematic richness is further explored through semiotic and thematic analysis, revealing how recurrent motifs, such as social hierarchy, innovation, and exploration are embedded in player choices and narrative outcomes. These are interpreted through the lens of game studies frameworks, including Aarseth’s (1997) ergodic literature, Juul’s (2005) half-real systems, and Bogost’s (2007) procedural rhetoric. The findings demonstrate how 80 Days reimagines Victorian culture by combining creative technology with historical authenticity, emphasizing intersections of gender, colonial, and class hierarchies through interactive engagement. This study contributes to game studies, digital humanities, and Victorian studies by demonstrating how digital games can retell historical myths while fostering critical thinking about the past and its continued relevance today.